The Effect of Giving Question And Getting Answer (GQGA) Learning Model on Students' Science Learning Outcomes at Grade IV of UPTD SD Negeri 122348 Pematangsiantar - Grace Catalina Sipayung; Melvin M. Simanjuntak; Hetdy Sitio (International Journal of Technology and Education Research, 2026)
This study aims to examine the effect of the Giving Question and Getting Answer (GQGA) learning model on students’ learning outcomes in the IPAS subject among fourth-grade students at UPTD SD Negeri 122348 Pematangsiantar in the 2025/2026 academic year. The study employed a quantitative approach using a pre-experimental method with a one-group pretest–posttest design. The research sample consisted of 24 fourth-grade students selected through a saturated sampling technique. The research instrument used was a multiple-choice test designed to measure students’ cognitive learning outcomes. Data were analyzed using the N-Gain test to determine the effectiveness of the learning model. The results showed that the average N-Gain score was 0.7133, with an average percentage of 71.33%, which falls into the high-effectiveness category. These findings indicate that the implementation of the GQGA learning model has a significant positive effect on improving students’ learning outcomes in IPAS. The model encourages active student participation through questioning and answering activities, which enhances understanding, critical thinking, and classroom engagement. Students become more involved in the learning process, rather than passively receiving information from the teacher. Therefore, it can be concluded that the Giving Question and Getting Answer (GQGA) learning model is effective in improving IPAS learning outcomes for fourth-grade students at UPTD SD Negeri 122348 Pematangsiantar. This model can be recommended as an alternative interactive learning strategy to enhance student achievement in elementary education.